Diversity and Potential Carbon Services of In-Situ Conservation Reserve in Gunung Sepuluh Timur Forest at Balikpapan, East Kalimantan - Adonis Muzanni; Tri Edhi Budhi Soesilo; Dwi Nowo Martono; Udi Syahnoedi Hamzah; Andri Wibowo; David Febraldo; Fatma Lestari (HAYATI Journal of Biosciences, 2022)
Establishing an in-situ conservation reserve is one of the strategic approaches to conserving an ecosystem and protecting it from immediate threats, including deforestation and land-use conversion. Kalimantan is one of the islands in Indonesia that is currently threatened by deforestation. To protect East Kalimantan diversity, mainly in Balikpapan, an in-situ conservation reserve has been established in Gunung Sepuluh Timur (GST) forest. In contrast, the information on tree diversity and how the presence of tree community within the forest can benefit the ecosystem are still limited. This research aims to assess the potential benefits and carbon storage of the GST conservation forest. The assessment method applied tree, pole, and sapling surveys combined with forest cover analysis using GIS and NDVI (Normalized Difference Vegetation Index) approaches. The GST contained 56 tree species, 25 pole species, and 16 sapling species. Diversity (H’) at tree stages was the highest (H’ = 0.759; 95%CI: 0.64-0.88) and H’ at sapling stages was the lowest (H’ = 0.719; 95%CI: 0.51-0.92). The carbon service potential of GST forest was 87.04 t C/ha on average. It was estimated that the economic benefits of GST in sequestering carbon based on the compliance market rate were equal to US$ 189,758/year.